The Effect of Capital Assistance, Financial Literacy, And Entrepreneurial Motivation on The Economic Welfare of Mustahik in The YBM Brilian Ro Pekanbaru - nanda ega Rupita; Muhammad Albahi; Mulia Sosiady (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of Capital, Financial Literacy, and Entrepreneurial Motivation on the Economic Welfare of mustahik beneficiaries of the Gerobak Bermakna Program at YBM BRILiaN RO Pekanbaru. The study tests the hypothesis that the three independent variables have a positive and significant effect on economic welfare, both partially and simultaneously. A quantitative approach with an explanatory research design was employed. The population, which also served as the sample, consisted of 169 mustahik selected using a total sampling technique. Data were collected through structured questionnaires using a Likert scale and analyzed using multiple linear regression at a 5% significance level. The results indicate that Business Capital (t = 2.217; p = .028), Financial Literacy (t = 6.406; p = .000), and Entrepreneurial Motivation (t = 3.349; p = .001) have a positive and significant effect on Economic Welfare. Simultaneously, the analysis shows F(3,165) = 66.626; p = .000 with an R² value of .548, meaning that 54.8% of the variance in economic welfare can be explained by the three variables. Financial literacy emerges as the most dominant variable. These findings imply that productive zakat programs should integrate capital assistance with continuous capacity building and entrepreneurial motivation development to sustainably enhance beneficiaries’ economic welfare.